2018
DOI: 10.2147/ppa.s188078
|View full text |Cite
|
Sign up to set email alerts
|

Substance use preferences and sexually transmitted infections among Canadian post-secondary students

Abstract: BackgroundIn Canada, substance use is one of the key predisposing factors that may lead to risky sexual behaviors among post-secondary students. There is considerable economic burden and significant public health concern posed by substance use and sexually transmitted infections (STIs). The purpose of this study was to examine the prevalence of substance use preferences (alcohol, cannabis, and other drugs) and its association with STIs among Canadian post-secondary students.Materials and methodsThis is a cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
(29 reference statements)
1
3
0
Order By: Relevance
“…The findings of a higher prevalence of high-risk drug use among those who reported sex work, previous STIs, and inconsistent condom use are consistent with the findings of previous studies [ 32 34 ]. Substance use disorder has a negative effect on the control of STIs by interfering with the user’s decision-making and favoring sexual practices with a higher risk of acquiring STIs.…”
Section: Discussionsupporting
confidence: 90%
“…The findings of a higher prevalence of high-risk drug use among those who reported sex work, previous STIs, and inconsistent condom use are consistent with the findings of previous studies [ 32 34 ]. Substance use disorder has a negative effect on the control of STIs by interfering with the user’s decision-making and favoring sexual practices with a higher risk of acquiring STIs.…”
Section: Discussionsupporting
confidence: 90%
“…In total, 11 publications satisfied the inclusion criteria. As there are countless articles (mostly cross-sectional studies, not included in our review) on associations between alcohol use and STIs (for a random selection, see Connor et al, 2015;Herrera et al, 2016;Hojilla et al, 2020;Liu et al, 2016;Soe et al, 2018), we based our review solely on cohort and case control studies.…”
Section: Resultsmentioning
confidence: 99%
“…Examining prevalence according to racial background is important because studies have shown that Black Canadians experience high levels of racial discrimination (Cénat, Hajizadeh, et al, 2022; Godley, 2018), an established risk factor for substance use (e.g., alcohol, cannabis, crack) as shown in studies conducted in the United States (U.S.; Assari et al, 2018; Clark et al, 2015; Metzger et al, 2017). Furthermore, a study among college students in Canada revealed that Black participants were the only racial group at higher risk of substance use compared to White students (Soe et al, 2018).…”
Section: The Present Studymentioning
confidence: 99%
“…, an established risk factor for substance use (e.g., alcohol, cannabis, crack) as shown in studies conducted in the United States (U.S.; Assari et al, 2018;Clark et al, 2015;Metzger et al, 2017). Furthermore, a study among college students in Canada revealed that Black participants were the only racial group at higher risk of substance use compared to White students (Soe et al, 2018).…”
mentioning
confidence: 95%